KAJIAN PRODUKSI JAGUNG DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI KASUS DI KABUPATEN SELUMA PROPINSI BENGKULU) - Cahyadinata, Indra; Iryansyah, Risqie (Jurnal AGRISEP, 2010)
This research was aimed to define the corn farmer's behaviour  in Seluma Regency of Bengkulu  Province on inputs and outputs allocation, and determine  of production factors influencing  corn production.  The research was located in three villages in Seluma Regency, namely Riak Siabun, Sido Luhur,  and Sumber Arum. Sixty two farmers were selected using stratified random sampling  method. In this research, the analitical description was used to analyse farmer  behaviour. In order to determine the input and output allocation of the corn productions,  this research used the function of production  Cobb-Douglas  approach. The result showed found that the behaviour of the farmers to choose corn was due to the corn was easy to sell and cultivate. However, the farmers  found  that it  is  hard to access some production factors,  such as seed, fertilizer,  and pesticide. Their prices were also high, and these were contradicted  to the product's  price which was low. Tis research also found that land area is the main factor that has a significant  impacts on production  while other factors were not.